Management of health services: A critical analysis of recent literature - Antonio, Perales Fabian Victor (Edelweiss Applied Science and Technology, 2026)
This study aimed to analyze and synthesize scientific evidence on health services management published between 2020 and 2025 in the Scopus and Scielo databases. A qualitative documentary review was conducted, selecting nine peer-reviewed articles based on predefined inclusion criteria related to relevance, methodological rigor, and thematic alignment. The findings reveal that health services management constitutes a multifaceted field shaped by contextual, institutional, and systemic factors. While Scopus shows a substantial volume of scientific production on this topic, Scielo presents a more limited number of publications, which may restrict the dissemination of accessible knowledge in certain regions. The reviewed studies consistently highlight that effective hospital management depends not only on process optimization and technological innovation but also on equity in service provision, workforce integration, and organizational leadership. Furthermore, continuous professional training, evidence-based decision-making, and patient-centered strategies emerge as key determinants of improved healthcare performance, although their implementation varies across health systems. In conclusion, strengthening health services management requires an integrated approach that balances efficiency, equity, and human resource development. These findings have important implications for policymakers and healthcare administrators seeking to design more inclusive, efficient, and sustainable health systems.